Pengaruh Jarḥ Wa Ta‘Dīl Terhadap Kekuatan Hukum Hadis (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
The hadith of the Prophet Muhammad (peace be upon him) is the second source of Islamic law after the Qur'an, which plays a central role in establishing Islamic teachings and laws. However, differences in the quality of narration require a scientific method to ensure the authenticity of hadith before it can be used as a sharia shari'ah argument. This article aims to analyze the concept and mechanism of jarḥ wa ta'dīl in assessing the quality of narrators and hadith, the influence of the results of jarḥ wa ta'dīl on the classification of hadith and its level of acceptance as sharia shari'ah argument, and its implications for the legal force of hadith in the istinbāṭ al-aḥkām process. This study uses a qualitative approach with a normative-descriptive library research method. Data were obtained from primary and secondary literature in the fields of hadith science and usul fiqh, then analyzed using content analysis and comparative techniques. The results of this study indicate that jarḥ wa ta‘dīl is the main methodological foundation in determining the validity of hadith through assessing the moral integrity (‘adālah) and intellectual rigor (ḍabṭ) of the narrator. This finding confirms that the results of jarḥ wa ta‘dīl directly influence the classification of hadith—ṣaḥīḥ, ḥasan, and ḍa‘īf—and determine its legal force as a source of Islamic law. In the contemporary context, the urgency of jarḥ wa ta‘dīl is increasing along with the massive dissemination of hadith through digital media, so that scientific verification is a necessity to maintain the validity of Islamic teachings.